Otimização de consumo energético em casas inteligentes com ESP32 e TagoIO - Rocha, Carlos Henrique Basali (Universidade Federal de São Carlos, 2025)
This work addresses energy management in smart homes, highlighting the problem of electricity waste and the need for efficient solutions for monitoring and optimizing consumption. The main objective is to develop and simulate a system based on the ESP32 and the TagoIO platform, using the MQTT protocol for real-time data transmission from sensors and actuators. The study is justified by the growing demand for energy efficiency and the accessibility of IoT and cloud computing technologies, which enable more effective control of household appliances. The methodology involves the implementation of a simulation and a prototype, where sensors collect temperature, humidity, and motion data and send the information to a dashboard in TagoIO, facilitating data visualization and analysis. The tests carried out demonstrated that the system can provide relevant information about the environment and controlled devices, allowing for a better understanding of usage patterns and contributing to more efficient and sustainable energy consumption.
Optimizing energy consumption in smart homes with ESP32 and TagoIO
Keywords: Internet das coisas; Internet of things; Gerenciamento de energia; Energy management; ESP32; TagoIO; MQTT; Monitoramento energético; Energy monitoring; Computação em nuvem; Cloud computing; ENGENHARIAS::ENGENHARIA ELETRICA::ELETRONICA INDUSTRIAL, SISTEMAS E CONTROLES ELETRONICOS; ENGENHARIAS::ENGENHARIA ELETRICA::MEDIDAS ELETRICAS, MAGNETICAS E ELETRONICAS; INSTRUMENTACAO; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::SISTEMAS DE COMPUTACAO